Implementation of the Digital Service System Policy at the Population and Civil Registration Office of Bandung Regency - Bambang Triana Prima; Yeti Rohayati; Diani Indah (INFOKUM, 2025)
This study analyzes the implementation of the Bedas Digital Service (BDS) policy system at the Population and Civil Registration Office (Disdukcapil) of Bandung Regency using the Van Meter and Van Horn (1975) model. BDS was launched as a response to weaknesses in the manual system for monitoring and supervising population administration services. This qualitative research, employing a single case study design, utilized in-depth interviews, participatory observation, and document analysis. Data were analyzed using Miles and Huberman’s interactive model, along with source and method triangulation. The findings show that BDS implementation achieved 75% of its target. Based on the six variables of the Van Meter and Van Horn model: the policy standards are clear, emphasizing efficiency, monitoring, and transparency; resources are supported by the regional budget (APBD) and free WiFi in 280 locations, although human resources remain limited (only 10 IT operators); vertical and horizontal communication runs effectively; Disdukcapil possesses adequate competence; the environmental conditions show strong political support but digital gaps persist among adult and elderly groups; and implementers’ dispositions are positive. Supporting factors include political backing, competent human resources, WiFi infrastructure, inter-agency coordination, and adoption by younger generations. Inhibiting factors involve server instability, limited personnel, digital divides, dependence on central systems, geographical blank spots, and cautious behavior among staff. BDS has successfully reduced illegal intermediaries, improved transparency (trust index rising from 65% to 88%), and increased time efficiency (from several months to 2–3 days). The one-day service target has not been fully achieved due to technical and operational challenges. Overall, BDS implementation shows significant progress but still requires infrastructure strengthening, additional personnel, and digital literacy programs for optimal outcomes.